Analysis of Waste Generation and Composition of Jampue Secondary Canal Saddang Irrigation Area - Eris Nur Dirman; Muh. Aris Arifin; Alwi Herywirawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Secondary irrigation channel of Jampue faced that garbage problem to environment and the sustainability of irrigation system. This study aims to determine the quantity, types, and composition of garbage in the channel in order to establish effective waste management for the irrigation channel. The methods followed the SNI 19-3964-1994. The result indicates that the amount of garbage is 0.006 kg/m²/day, with an average volume of 402.225 liters/day or 0.030 liters/m²/day. They include water hyacinth (44.42%), wood waste (20.97%), and plastic (34.61%). Based on the results, effective waste management strategies include the provision of waste infrastructure for the irrigation channel, changing community behavior to prevent dumping garbage into the channel, and the reuse of water hyacinth and recycling of plastic waste.